DL‐β‐Aminobutyric acid application negatively affects reproduction and larval development of the rosy apple aphid, Dysaphis plantaginea, on apple. Issue 1 (11th March 2016) - Robert, Philippe; Braud, Ferréol; Aligon, Sophie; Brisset, Marie‐Noëlle
Abstract: The rosy apple aphid, Dysaphis plantaginea (Passerini) (Hemiptera: Aphididae), is one of the major pests of European apple orchards, commonly controlled by the use of synthetic insecticides. In the present work, the non‐protein amino acid DL‐β‐aminobutyric acid (BABA), known to induce plant resistance against a wide range of abiotic and biotic stresses, has been tested for its protective effect against this pest on apple. We first verified the lack of any contact effect of BABA on the insect itself. Next we applied BABA as a soil drench to apple and monitored its effect on the population development of aphids after artificial infestation. We demonstrated that BABA strongly reduced the population growth and that this compound severely affected various life‐history characteristics of the aphid such as female longevity and fecundity, nymph mortality, and larval development.